2022
DOI: 10.1021/acs.molpharmaceut.2c00051
|View full text |Cite
|
Sign up to set email alerts
|

Combined Probe Strategy to Increase the Enzymatic Digestion Rate and Accelerate the Renal Radioactivity Clearance of Peptide Radiotracers

Abstract: High and sustained renal radioactivity accumulation is a major challenge in peptide-based radionuclide imaging and therapy. However, neutral endopeptidase (NEP)-based enzymatic hydrolysis to release and excrete the radioactive fragments has been proven to be an effective and promising way to reduce renal accumulation. Despite the improvement, the effect is still far from being satisfactory. To further reduce kidney uptake, we studied the relationship between the enzymatic reaction rate and the substrate concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Although recent studies were focused on optimizing the linker sequences toward an enhanced enzymatic cleavage rate, 39,40 no quantitative data on the distinct substrate potential toward NEP or other brush border membrane enzymes are reported, which would lay the basis for a rationalized use of this strategy. Furthermore, the concept of cleavable linkers was predominantly applied to antibody derivatives and large peptides, such as exendin-4, 39,41,42 but only few studies are reported on adapting this strategy to small molecules or peptides.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although recent studies were focused on optimizing the linker sequences toward an enhanced enzymatic cleavage rate, 39,40 no quantitative data on the distinct substrate potential toward NEP or other brush border membrane enzymes are reported, which would lay the basis for a rationalized use of this strategy. Furthermore, the concept of cleavable linkers was predominantly applied to antibody derivatives and large peptides, such as exendin-4, 39,41,42 but only few studies are reported on adapting this strategy to small molecules or peptides.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although recent studies were focused on optimizing the linker sequences toward an enhanced enzymatic cleavage rate, , no quantitative data on the distinct substrate potential toward NEP or other brush border membrane enzymes are reported, which would lay the basis for a rationalized use of this strategy. Furthermore, the concept of cleavable linkers was predominantly applied to antibody derivatives and large peptides, such as exendin-4, ,, but only few studies are reported on adapting this strategy to small molecules or peptides. , Herein, we synthesized a series of 64 Cu-labeled tri- and tetrapeptides and quantified their suitability to act as neprilysin substrates (NES) in a radiometric assay using recombinant NEP, which led to the exploration of the structural features that drive the cleavage rate.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is insertion of a cleavable linker (such as glycyl-lysine “GK” or methionine-valine-lysine “MVK” sequences) between the peptide/protein and the radiolabeled chelate moiety that is recognized and cleaved by enzymes on the lumen of renal tubules. , Consequently, the radionuclide-bearing portion of the molecule would be emancipated from the peptide/protein and excreted from the kidneys to the bladder without reabsorption. These enzyme-activated linkers are very sensitive to the molecular structure around the recognition sequence, and it is not trivial to perform detailed enzyme kinetics to validate the activity and selectivity of a new derivative. Further, it is common for nontargeted enzymes in the blood or other healthy tissues to have some activity toward many of these cleavable linkers, making their application to new radiopharmaceuticals nontrivial.…”
Section: Introductionmentioning
confidence: 99%